Systematic study of Co-free LiNi0.9Mn0.07Al0.03O2 Ni-rich cathode materials to realize high-energy density Li-ion batteries - Seenivasan, Manojkumar; Yang, Chunchen; Wu, She–Huang; Chang, Jeng Kuei; Jose, Rajan
The growing use of EVs and society's energy needs require safe, affordable, durable, and eco-friendly high-energy lithium-ion batteries (LIBs). To this end, we synthesized and investigated the removal of Co from Al-doped Ni-rich cathode materials, specifically LiNi0.9Co0.1Al0.0O2 (NCA-0), LiNi0.9Mn0.1Al0.0O2 (NMA-0), LiNi0.9Mn0.07Al0.03O2 (NMA-3), intending to enhance LIB performance and reduce the reliance on cobalt, a costly and scarce resource. Our study primarily focuses on how the removal of Co affects the material characteristics of Ni-rich cathode material and further introduces aluminum into the cathode composition to study its impacts on electrochemical properties and overall performance. Among the synthesized samples, we discovered that the NMA-3 sample, modified with 3 mol% of Al, exhibited superior battery performance, demonstrating the effectiveness of aluminum in promoting cathode stability. Furthermore, the Al-modified cathode showed promising cycle life under normal and high-temperature conditions. Our NMA-3 demonstrated remarkable capacity retention of ∼ 88 % at 25 °C and ∼ 81 % at 45 °C after 200 cycles at 1C, within a voltage range of 2.8–4.3 V, closely matching the performances of conventional NCM and NCA cathodes. Without cobalt, the cathodes exhibited increased cation disorder leading to inferior rate capabilities at high C-rates. In-situ transmission XRD analysis revealed that the introduction of Al has reduced the phase change and provided much-needed stability to the overall structure of the Co-free NMA-3. Altogether, the findings suggest that our aluminum-modified NMA-3 sample offers a promising approach to developing Co-free, Ni-rich cathodes, effectively paving the way toward sustainable, high-energy–density LIBs.